2004
DOI: 10.1021/jf0497298
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxins from the Leaves of Ruta graveolens

Abstract: Bioassay-guided fractionation of the ethyl acetate extract of Ruta graveolens (common rue) leaves led to the isolation of the furanocoumarins 5-methoxypsoralen (5-MOP), 8-methoxypsoralen (8-MOP), and the quinolone alkaloid graveoline as phytotoxic constituents. Graveoline and 8-MOP substantially inhibited growth of Lactuca sativa (lettuce) seedlings and reduced chlorophyll content at 100 microM; this effect was not due to a direct effect on chlorophyll synthesis. Radical growth of L. sativa was inhibited by 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 18 publications
0
36
0
5
Order By: Relevance
“…Ruta graveolens plants and cell cultures accumulate linear furanocoumarins (psoralens) and acridone or furoquinoline alkaloids (Wolters and Eilert 1981;Zobel and Brown 1989;Stashenko et al 2000;Poutaraud et al 2000;Milesi et al 2001;Oliva et al 2003;Hale et al 2004;Kuzovkina et al 2004;Michael 2007) as the predominant secondary metabolites besides aliphatic 2-ketones (De Feo et al 2002) and flavonoids (Wolters and Eilert 1981;Saieed et al 2006;Harborne and Baxter 1999). Acridone alkaloids were detected in all organs particularly in endodermal and vascular tissues (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Ruta graveolens plants and cell cultures accumulate linear furanocoumarins (psoralens) and acridone or furoquinoline alkaloids (Wolters and Eilert 1981;Zobel and Brown 1989;Stashenko et al 2000;Poutaraud et al 2000;Milesi et al 2001;Oliva et al 2003;Hale et al 2004;Kuzovkina et al 2004;Michael 2007) as the predominant secondary metabolites besides aliphatic 2-ketones (De Feo et al 2002) and flavonoids (Wolters and Eilert 1981;Saieed et al 2006;Harborne and Baxter 1999). Acridone alkaloids were detected in all organs particularly in endodermal and vascular tissues (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Khellin and visnagin are closely related furanochromones. 5-MOP and 8-MOP are structurally closely related furocoumarins that have been previously isolated in our laboratory from the ethyl acetate extract of Ruta graveoleans leaves and roots [12]. Even though khellin has been shown to be phototoxic, Kagen et al [15] have shown that khellin had no toxicity towards Ae.…”
Section: Resultsmentioning
confidence: 95%
“…The two furanocoumarins 5-MOP and 8-MOP (Figure 2) (that have been isolated by us previously from Ruta graveolens) [12] also showed weaker activities in the adulticide assay against both strains of mosquitoes comparable to khellin and visnagin. The positive control permethrin showed 100% mortality of ORL strain adult mosquitoes at 1.8 ng/mosquito whereas the PR strain adult mosquitoes showed 60% mortality at 17.8 ng/mosquito.…”
Section: Resultsmentioning
confidence: 97%
“…Means followed by the same letter within the column are not significantly different at p < 0.05. the quinolone alkaloid graveoline isolated from rue extracts cause growth reduction through cell leakage and inhibition of cell division (Hale et al, 2004). Ethanolic and aqueous extracts of fennel seed contain a high phenolic content (Oktay et al, 2003), while major phenolic compounds of methanolic extract of fennel plant material include caffeoylquinic, chlorogenic, dicaffeoylquinic, and rosmarinic acids (Križman et al, 2007).…”
Section: Furanocoumarins 5-methoxypsoralen (5-mop) 8-methoxypsoralmentioning
confidence: 99%